2019
DOI: 10.13005/msri/160108
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Microstructure Properties on Al-Cu Joint processed by Friction Stir Welding: The effect of Tilt Angle Tool

Abstract: The tilt angle tool on Aluminum A5083 and Copper C11000 joint processed by Friction Stir Welding (FSW) was observed in this study. The rotation speed and transverse speed were used as a parameter process for 2500 rpm and 30 mm/min, respectively. The tensile test and microstructure observation were carried out to determine the tensile strength and metal flow on Al-Cu joint, respectively. The result shows that the highest tensile strength was in 2o tilt angle tool for 105 MPa. Its fracture surface was more close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…e mechanical and microstructure properties were performed to examine ultimate tensile strength values and metal movement properties toward the welded FSW of the Al-Cu welded joint. e authors found at 2 tilt angles, at 105 MPa, high tensile strength was obtained and the fracture surface was found nearly closer to Al and obtained brittle formation [12]. Anbukkarasi and Kailas used AA2024 and pure copper workpieces of 5 mm thick buttwelded configurations for various tool offset positions, with plain, threaded tool geometry, and plate positions.…”
Section: Introductionmentioning
confidence: 98%
“…e mechanical and microstructure properties were performed to examine ultimate tensile strength values and metal movement properties toward the welded FSW of the Al-Cu welded joint. e authors found at 2 tilt angles, at 105 MPa, high tensile strength was obtained and the fracture surface was found nearly closer to Al and obtained brittle formation [12]. Anbukkarasi and Kailas used AA2024 and pure copper workpieces of 5 mm thick buttwelded configurations for various tool offset positions, with plain, threaded tool geometry, and plate positions.…”
Section: Introductionmentioning
confidence: 98%
“…79 Jupri et al found the highest joint strength at 2°tilt angle that allowed good Al-Cu flow in NZ. 80 Influences of tool tilt angle are as follows:…”
Section: Outcomes Of Placing Cu On Asmentioning
confidence: 99%
“…79 Jupri et al found the highest joint strength at 2° tilt angle that allowed good Al-Cu flow in NZ. 80 Influences of tool tilt angle are as follows: The correct tilt angle ensures that material stirred by the tool pin is retained by the tool shoulder and pushed from top to bottom and front to back under the FSW tool. With the aid of the tilt angle, plastically deformed material is compressed under the FSW instrument. Within the stir region, the tool tilt angle allows the plasticized material to flow in both horizontal and vertical directions. The defects are filled by forging material downward due to large tilt angle A greater tilt angle produced a tighter weld and reduced the flash effect. As the axial plunge force is increased, a higher tilt angle allows Cu to freely flow in Al. Consequently, there is excellent metallurgical bonding between Cu and Al. The formation of massive and different forms of intermetallic increases the joint hardness due to high heat input in the stir zone at a wide tilt angle. Hence, the selection of optimum tool tilt angle is also necessary.…”
Section: Strategies For Fsw Of Al-cumentioning
confidence: 99%
“…With an increase in tool rotational speed and the tool offset at the center and AA6101 side, the UTS value increases. At higher speeds, the tool offset towards the C11000 side, and the UTS value decreases [40][41][42][43].…”
Section: Evaluation Of Ultimate Tensile Strength (Uts) From the Exper...mentioning
confidence: 99%